Combined gasification of lignite coal: thermodynamic and application study - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Chavan, Rank N. (Journal of the Taiwan Institute of Chemical Engineers, 2014)
Combined gasification (a combination of steam gasification and CO2 gasification) without air is an important process for research in coal gasification to reduce the steam generation energy in the gasification system and also to enhance the slow CO2 gasification reaction. A thermodynamic study involving the effect of temperature, pressure and feed CO2 and steam ratios in gasification of lignite coal was studied in this paper. The product generation trends of syngas and methane with carbon (in coal) conversion were studied in detail. The carbon (in lignite coal) was converted completely at a lower temperature than pure carbon in the combined gasification. Some applications of the gasifier product gas were also studied. Combined gasification offers great advantages to produce syngas of exact ratio in one step for use in petrochemical manufacture and fuel cell systems. The complete carbon (in coal) conversion occurred beyond the thermoneutral gasification temperature in the study. The combined gasification process was a useful way for CO2 utilization reducing the net CO2 emission to the atmosphere. (C) 2013 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Coal gasification; Coal to syngas; Combined gasification; Thermodynamic study